2022
DOI: 10.1111/bcp.15301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacist intervention in reducing vancomycin‐associated acute kidney injury: A systematic review and meta‐analysis

Abstract: Aims The aim was to quantify the relationship between pharmacist intervention and vancomycin‐associated acute kidney injury (AKI). Methods Electronic databases were searched up to August 2020 for meta‐analyses of cohort studies and/or randomized controlled trials. Studies that compared the incidence of AKI in patients between post‐ and prepharmacist intervention were investigated. The primary outcome was incidence of AKI. We also evaluated the influence of pharmacist intervention in risk factors of vancomycin‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In previous reports, TDM was evaluated for appropriate management using VCM blood concentration values [18]. On the other hand, in this study using reimbursement, although it was clear that blood concentration management was measured, the control status of the VCM concentration values was unknown.…”
Section: Discussionmentioning
confidence: 85%
“…In previous reports, TDM was evaluated for appropriate management using VCM blood concentration values [18]. On the other hand, in this study using reimbursement, although it was clear that blood concentration management was measured, the control status of the VCM concentration values was unknown.…”
Section: Discussionmentioning
confidence: 85%
“…The technology for TDM of vancomycin is well established and the guidelines are clear in the recommendations for the management of vancomycin monitoring, however, the status of monitoring in clinical practice is not satisfactory. We previously conducted a meta-analysis including 19 studies with 2,598 patients from developed countries such as the United States, Japan, Australia, and New Zealand, and developing countries such as China and India, and showed that the mean vancomycin trough concentration attainment rate was 34.3% under the conventional physician-led model of care (Kunming et al, 2023). Factors contributing to the unsatisfactory status of monitoring under physician-led vancomycin TDM included negative perception towards prescription guidelines, lack of knowledge regarding TDM guidelines, the hierarchy of medication management, work pressure, and ineffective communication among healthcare providers (Abdel Jalil et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we suggest clinical care teams should increase the involvement of clinical pharmacists. Our previously published study showed that pharmacist intervention in vancomycin treatment significantly decreased the rate of VA-AKI while improving efficacy and reducing mortality (Kunming et al, 2023). Clinical pharmacists are experts in medication therapy management, and many hospitals, mainly in the United States, have established the model of pharmacist managing vancomycin dosing and monitoring, which is worthy of emulation by hospitals in other countries (Kunming et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of target attainment seen with current vancomycin dosing and monitoring practices provides an opportunity for improvement. Previous studies have demonstrated that pharmacist-driven vancomycin dosing and monitoring can have beneficial outcomes such as improvements in target attainment, reduction in vancomycin-induced AKI, and lower rates of mortality [ 16 , 17 ]. A recent meta-analysis was conducted to determine the relationship between pharmacist intervention and vancomycin outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis was conducted to determine the relationship between pharmacist intervention and vancomycin outcomes. The meta-analysis included 34 studies and almost 20,000 participants and found that pharmacist intervention in vancomycin management resulted in significantly lower rates of AKI (OR 0.52, 95% CI; [0.41, 0.67], p < 0.00001), significantly higher rates of target attainment (OR 2.86, 95% CI [2.23, 3.67], p < 0.00001), and significantly lower rates of mortality (OR 0.47, 95% CI [0.31, 0.72], p = 0.0004) [ 16 ]. Another retrospective cohort study evaluated rates of monitoring compliance after a pharmacist-driven vancomycin monitoring initiative was implemented.…”
Section: Discussionmentioning
confidence: 99%